IMPACT OF ABIOTIC FACTORS AND ENVIRONMENTAL CONTAMINATION ON INSECT DIVERSITY OF AGRO-ECOSYSTEM: A REVIEW - KAUR, AMRIT DEEP; KAUR, KAMALPREET (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The interaction of abiotic (temperature, humidity, rainfall, soil texture, geographical area, pollutants) and biotic (crop plants, weeds, insect pests, and humans) components determine the agro-ecosystem environment. Abiotic factors modulate the effect of biotic factors, but the most dangerous results are observed when biotic factors control abiotic factors. Human (biotic factor) activities like industrialization, uncontrolled urbanization, use of insecticide, pesticide and excessive burning of fossil fuels polluting air we breathe, water we drink and soil we sow. Above aforementioned activities are responsible for adverse effect on the environment of the area. Environmental pollution and other anthropogenic activities are major cause of climate change. The global planetary warning, altered rainfall pattern, precipitation, humidity effects multiple ecosystems. Climate changes effects global warming, environmental degradation, flora and fauna on earth. This article, enlighten farmers, horticulturist and researchers about climatic changes and their effects on insect diversity. As crop growers must contend with a serious threat from insect pests. Further research on climate change, seasonal variation, environmental contamination, and their impact on insect pests is an urgent need of the hour. The impact of seasonal changes on crop production, as mediated by changes in the populations of serious insect pests, must be carefully considered while developing and implementing pest management strategies. Such pest management strategies should be used to reduce crop loss while not compromising food quality or the environment.